ATLAS OF THE SEA SURFACE TEMPERATURE OVER THE ATLANTIC INTERTROPICAL BASIN USING DATA FROM THE NOAA-14 SATELLITE (19952001) - Antonio Geraldo Ferreira; Paulo Travassos (Gayana, 2004)
The objective of this paper is to present the "Atlas of the Sea Surface Temperature over the Atlantic Intertropical Basin by Using Data from the NOAA-14 Satellite (19952001)". In the Atlas, detailed information about the procedures utilized to retrieve SST from NOAA-14/AVHRR, over the Atlantic Ocean in the area encompassed by latitudes 10 N-20 S and longitudes 50 W-20 W, were compiled. Also included in the Atlas, is the complete set of monthly SST images and monthly historical average in the period between 1995 and 2001.Based on these images, short description of the SST patterns over the area mentioned before is made. The Atlas includes 2 CD's, one of which containing approximately 1250 images already processed, in jpg format, of the SST fields (daily, monthly and monthly mean), includies the software that enables to make the visualization, animation and some basic statistics over the images. The other CD contains the raw SST data base